IV thrombolysis for treatment of patients with stroke upon awakening: Yes? No?. Issue 4 (August 2015) - Adams, Harold P.
Abstract : Summary: Current guidelines recommend IV administration of recombinant tissue plasminogen activator (rtPA) to carefully selected patients who can be treated within 4.5 hours of ischemic stroke onset. Patients whose neurologic symptoms are discovered upon awakening (wake-up stroke) generally are not given rtPA because of the uncertainty about the time of stroke onset. This group of patients may be relatively large. Preliminary reports suggest that patients with wake-up stroke who can be treated within 4.5 hours of discovery may respond similarly to patients with an established time of stroke onset. Clinical trials, which are selecting patients to treat primarily based on imaging surrogates, are under way. Pending the results of these trials, data about the utility of clinical or imaging findings that would identify those patients who could be treated and information about the safety and efficacy of IV rtPA in this situation are not available.